PENGATURAN DAN TANTANGAN PENGGUNAAN E-VOTING PADA PENYELENGGARAAN PEMILIHAN KEPALA DAERAH DI INDONESIA - Fanila Kasmita Kusuma (Media Bina Ilmiah, 2024)
The ease of holding post-conflict local elections in Indonesia is felt by the e-voting system in the process of holding the post-conflict local elections. this is because human performance can be partially represented in e-voting to save energy and time. However, its implementation in Indonesia has collided with the regulation and the challenges of the implementation itself. This study aims to find out how to regulate and handle the implementation of e-voting in Indonesia. The method used is qualitative with a literature approach in order to obtain descriptive results. As for the results of this study, that the regulation of e-voting in elections is still not clear in the legislation, while the reference that can be used is the decision of the Constitutional Court Number 147/PUUVII/2009, namely the use of e-voting is not prohibited as long as it does not violate the principles of the general election. overflow and fair. The challenges in its implementation are more in the natural resource unpreparedness sector and the inequality of the internet network in every region in Indonesia